EFEK PEMAKAIAN LARUTAN DAUN SIRSAK (ANNONA MURICATA L) SEBAGAI BIOPESTISIDA TERHADAP TINGKAT SERANGAN HAMA ULAT PLUTELLA XYLOSTELLA DAN BIOMASSA KOL BUNGA - Bukhari, Bukhari; Handayani, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
The research was conducted at the experimental farm of Agricultural Faculty of the University of Jabal Ghafur Indrajaya Pidie district which lasted from August to November 2023 with the aim to determine the effect of soursop leaf extract against Plutella xylostella intensity of pest attacks and heavy wet/ cauliflower crop production. The design used in this study is Randomized Design Group (RAK) with six treatments and four replications (blocks), such treatment is the 0 (control or without application), soursop leaf extraxt concentration of 5.0 ; 10.0 ; 15.0 ; 20.0 and 25.0 % solution. The parame ters observed intensity of the attacks the caterpillar larvae of Plutella xylostella, and the Kol Flower Biomass production. These results indicate that the application of sour sop leaf extract is very significantly on the intensity of the attack Plutella xylostella and biomass of cauliflower production. Plutella xylostella larvae attack intensity is found at the highest concentration of 25.0 % solution is 4.11%, while the intensity of the attack Plutella xylostella larvae found at the lowest concentration of 5.0 % solution is 8.27%, on the other hand, the heaviest cauliflower biomass was found at a concentration of 25.0 % soursop leaf extract solution, namely 970 g/plot, while the lowest biomass was found at a control treatment (without aplication sour sop leaf extract solution or 0 % solution), with biomass produktion is 620 g/plot.